Potret Objek Hukum Islam: Tinjauan Klasik dan Kontemporer - Abidin Lingga, Umma; Ananda Arfa, Faisar (State of Islamic Institute Langsa, 2023)
This paper looks at the object of law from the perspective of Islamic law the concept of ushul fiqih (Islamic legal philosophy). This study is based on an in-depth study of Islamic law sources oriented towards ushul fiqih. The method used is literature with a data collection system to mix sources that study the science of ushul fiqih, from classical books to mutaakhir books. From the results of the author's search that the object of the law is the act or action of a person who is already mukallaf (legally capable). However, it depends largely on the condition that the deeds of a mukallaf be considered as a legal object or not. The main condition is that a person knows exactly about the deed from the side of the law and the method of its execution. Besides that, there is an element of ability and intentionality when doing so. The object of law is not limited to mere action but rather that everything related to deeds, utterances, neglects, and also azam (strong desires that are in mind).